Triplophysa pseudostenura, a new nemacheiline loach (Cypriniformes: Balitoridae) from the Yalong River of China - He, Chunlin; Zhang, E; Song, Zhaobin (Zootaxa, 2012)
A new species of nemacheiline loach, Triplophysa pseudostenura, is described from the Yalong River, a tributary of theupper Yangtze River drainage in China. Previous collectors misidentified the species as T. stenura. Triplophysapseudostenura can be separated from T. stenura and other valid species of Triplophysa by the following combination ofcharacters: body smooth and without scales; head tapering; lips thin and smooth; trunk and caudal peduncle slender,laterally compressed; depth of caudal peduncle tapering posteroventrally approaching caudal fin; posterior chamber of gasbladder reduced or absent; intestine short, forming a zigzag loop posterior to bottom of ‘U’-shaped stomach; insertion of pelvic fins anterior to dorsal-fin origin; caudal fin deeply concave.